Cellulase activity and age-based variation of intestinal microbiota in Hezuo pigs - Liang, Yuhao; Wang, Fei; Jia, Rui; Li, Jie; Wang, Longlong; Li, Yajuan; Li, Yao; Gun, Shuangbao; Yang, Qiaoli (Frontiers in Microbiology, 2025)
IntroductionTo examine the fiber-degrading enzyme activity and the changes of intestinal microbiota in Hezuo pigs across different age stages.MethodsFecal samples from 36 semi-grazed Hezuo pigs across five growth stages were collected for cellulase activity and 16S rRNA gene sequencing analysis.ResultsThe results showed that the cellobiase activity in adult Hezuo pigs was markedly higher than in other groups (p < 0.01). The intestinal microbiota of Hezuo pigs was predominantly composed of Firmicutes and Bacteroidetes. The prevalence of Proteobacteria of nursing piglets was significantly higher compared to other stages (p < 0.05), which might be related to protein degradation. Prevotella_NK3B31_group was a shared dominant genus across at all age stages, while Ruminococcaceae_UCG-005 dominated during the weaning, growth, fattening and adult stages. Its cellulose-degrading enzyme secretion capacity enhanced with age to meet the high-fiber dietary demands of Hezuo pigs. Functional prediction of intestinal microbiota in adjacent age groups using PICRUSt revealed that the differences between lactating piglets and weaned piglets were primarily due to the enrichment of various metabolic pathways functional genes, while differences between fattening pigs and adult sows were negligible. Adult boars showed significant enrichment in amino acid metabolism, energy metabolism, and nucleotide metabolism pathways compared to fattening piglets.DiscussionThese results reveal the age-related dynamic development of intestinal microbiota in Hezuo pigs, providing novel insights into the mechanism of their roughage tolerance.